Optical engineering of diamond - Mildren, Richard P.; Rabeau, James; Wiley eBooks (Weinheim : Wiley-VCH Verlag GmbH & Co. KGaA, 2013)
"This is the first comprehensive book on the engineering of diamond optical devices. It will give readers an up-to-date account of the properties of optical quality synthetic diamond (single crystal, nanodiamond and polycrystalline) and reviews the large and growing field of engineering of diamond-based optical devices, with applications in quantum computation, nano-imaging, high performance lasers, and biomedicine. It aims to provide scientists, engineers and physicists with a valuable resource and reference book for the design and performance of diamond-based optical devices."--
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Diamonds; Diamonds, Industrial -- Optical properties; Optical engineering; Optical films; TECHNOLOGY & ENGINEERING -- Optics; Electronic books